Solving time gap problems through the optimization of detecting stepping stone algorithm - Omar, Mohd. Nizam; Maarof, Mohd. Aizaini; Zainal, Anazida (IEEE Engineering in Medicine and Biology Society, 2004)
This paper describes an analysis of detecting stepping stone algorithm to defeat the time gap problem. It is found that current algorithm of detecting stepping stone is not optimized. Several weaknesses are identified and suggestions are proposed to overcome this problem. The suggestions are applied in the improved algorithm. Since the detecting stepping stone is listed as one of the response technique, it is suggested that the improved algorithm should be used as a remedial to the time gap problem.